From Protohypericin to Hypericin: Photoconversion Analysis Using a Time-Resolved Thermal Lens Technique. Issue 8 (August 2019) - Camargo, Vinicius G.; Zanuto, Vitor S.; Astrath, Nelson G. C.; Caetano, Wilker; Hioka, Noboru; Pereira, Paulo C. S.; Gonçalves, Renato S.; Lukasievicz, Gustavo V. B.; Herculano, Leandro S.; Malacarne, Luis C.
Hypericin (Hyp) is a natural compound with interesting photophysical and pharmacological properties, which has been used in photodynamic therapy and photodynamic inactivation of microorganisms. Its synthesis is based on a series of chemical processes that ends with a light–drug interaction by the photoconversion of protohypericin (pHyp) to Hyp. Although this photosensitizer is used in a variety of medical applications, the photophysical and photochemical mechanisms involved in the final step related to the photo production of Hyp are not completely understood at the molecular level. Protohypericin concentration, solvents, light irradiation under different wavelengths, and a sort of variables could play an important role in predicting the yielding of this photoconversion process. Here, we used the high-sensitive and remote measurement characteristics of the time-resolved thermal lens technique to investigate the relation between the light-induced photoconversion rate of pHyp to Hyp and the initial concentration pHyp. The results show a linear dependence of the photoreaction rate with the concentration of pHyp, indicating that the overall reaction process includes steps comprising the formation of distinct intermediate species. We demonstrate the applicability of the thermal lens technique for the photochemical characterization of photosensitive drugs at low concentration levels.